Pemberdayaan Ekonomi Petani Pasca Bencana Berbasis Inovasi Sosial Melalui Sociopreneur di Desa Supiturang Kabupaten Lumajang - Hijri, Yana Syafriyana; Sulistyono, Setyo Wahyu; Kurniawan, Wahyudi; Salam, Abdus (Civiliza Publishing, 2024)
The economic empowerment of farmers in disaster-affected areas or survivors is certainly a problem in the post-disaster phase during rehabilitation and reconstruction, one of which is the economic sustainability of the community so that they can still return to the new normal life. This is what happened in Supiturang Village, Pronojiwo District, where after the eruption of Mount Semeru, many residents lost their jobs, agricultural production decreased, including psychological conditions due to the trauma of the earthquake disaster. Social innovation as